Recycling oriented vertical vibratory separation of copper and polypropylene particles - Wang, Zheng; Miles, Nicholas J.; Wu, Tao; Gu, Fu; Hall, Philip (Elsevier, 2016)
Vibration has been employed in various engineering processes for material handling. The famous Brazil nut effect, large particles tend to rise to the top under vibration, initiates various research about vibration induced particle segregation. Particle size and density are two determining factors for their behaviour under vibration. Previous research in University of Nottingham proves vertical vibratory separation to be a promising environmental friendly mechanical separation method for recycling metallic fraction from shredded Waste Electric and Electronic Equipment (WEEE) stream. A pilot scale thin cell vibratory separator has been developed to investigate the potential for WEEE recycling applications. Shredded copper and polypropylene particles have been chosen to mimic metallic and non-metallic fractions in WEEE. Vibratory separation experiment with controlled environment and addition of solid lubricant are presented in this paper. The result demonstrates the effect of relative humidity and solid lubricant on improving flowability of granular system hence successful vibratory separation. The proposed mechanisms for the presence of moisture and solid lubricant are lubricant effect and elimination of static electricity.